Implementation of the optometry Aboriginal and Torres Strait Islander health curriculum framework - Pecar, Kate D.; Hopkins, Shelley; Anderson, Peter J.; Rallah-Baker, Kristopher R.D.; Bentley, Sharon A. (Clinical and Experimental Optometry, 2024)
Clinical relevance: There is now an Optometry Council of Australia and New Zealand (OCANZ) accreditation requirement for Australian and Aotearoa New Zealand optometry programs to ensure students can provide culturally safe care for First Nations Peoples. To assist programs, OCANZ developed the Optometry Aboriginal and Torres Strait Islander Health Curriculum Framework (Optometry Framework). Background: The objective of this study was to evaluate early progress towards the implementation. Methods: All seven Australian optometry programs were invited to complete a modified version of the OCANZ curriculum mapping tool. Where available, online unit outlines were reviewed to verify and supplement the data. Curriculum maps were synthesised using qualitative content analysis. Results: None of the five participating programs had a standalone Aboriginal and Torres Strait Islander health unit; instead, programs were integrating content into core units. Only 25% of the units with relevant content had a directly related learning outcome. All programs had at least some content that was either directly or indirectly related to each of the Optometry Framework themes, and included some content related to novice and intermediate levels of learning. Four programs had content related to entry to practice levels of learning. The average total duration of directly related content in programs (excluding clinical placements) was 18 hours. Not all programs offered an Aboriginal and Torres Strait Islander health setting clinical placement opportunity. Directly related assessment was minimal in most programs, where the format was predominantly reflective journals or questions within written examinations. Conclusion: Progress has been made in implementing the Optometry Framework; however, further efforts are required. Programs need to integrate additional directly related learning outcomes, content (particularly entry to practice level learning), and assessment. Further curriculum enhancements will improve the likelihood of optometry ...